Surface Characteristics of Nanoparticles Determine Their Intracellular Fate in and Processing by Human Blood–Brain Barrier Endothelial Cells In Vitro - Georgieva, Julia V (Nature Publishing Group, 2011)
A polarized layer of endothelial cells that comprises the blood–brain barrier (BBB) precludes access of systemically administered medicines to brain tissue. Consequently, there is a need for drug delivery vehicles that mediate transendothelial transport of such medicines. Endothelial cells use a variety of endocytotic pathways for the internalization of exogenous materials, including clathrin-mediated endocytosis, caveolar endocytosis, and macropinocytosis. The different modes of endocytosis result in the delivery of endocytosed material to distinctive intracellular compartments and therewith correlated differential processing. To obtain insight into the properties of drug delivery vehicles that direct their intracellular processing in brain endothelial cells, we investigated the intracellular processing of fixed-size nanoparticles in an in vitro BBB model as a function of distinct nanoparticle surface modifications. Caveolar endocytosis, adsorptive-mediated endocytosis, and receptor-mediated endocytosis were promoted by the use of uncoated 500-nm particles, attachment of the cationic polymer polyethyleneimine (PEI), and attachment of prion proteins, respectively. We demonstrate that surface modifications of nanoparticles, including charge and protein ligands, affect their mode of internalization by brain endothelial cells and thereby their subcellular fate and transcytotic potential.